If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 5 + -2y = 6y + -15 Reorder the terms: 5 + 4y + -2y = 6y + -15 Combine like terms: 4y + -2y = 2y 5 + 2y = 6y + -15 Reorder the terms: 5 + 2y = -15 + 6y Solving 5 + 2y = -15 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 5 + 2y + -6y = -15 + 6y + -6y Combine like terms: 2y + -6y = -4y 5 + -4y = -15 + 6y + -6y Combine like terms: 6y + -6y = 0 5 + -4y = -15 + 0 5 + -4y = -15 Add '-5' to each side of the equation. 5 + -5 + -4y = -15 + -5 Combine like terms: 5 + -5 = 0 0 + -4y = -15 + -5 -4y = -15 + -5 Combine like terms: -15 + -5 = -20 -4y = -20 Divide each side by '-4'. y = 5 Simplifying y = 5
| 11a+3=14a-2 | | 7-4.9m=15+7.6m | | 4c-(c-4)=9c+5 | | 2(6x-9)=3(x+5) | | 1.02u+2.45=7.583 | | -4-3p+4p=-2 | | 4(3ab)-2(a+10b)= | | 6x+1=6x+8 | | -3x-5=-2x-15 | | 6y=-66 | | t^2-3t-1=0 | | 1.5m-14=m+13 | | 7(1-x)=9(1+2x)+4 | | 4=9-3(2x+1)-5x | | x^2-14x+49-4y^2=0 | | 4p+3p=9p-14 | | 14(y+2)=7(2y-6) | | 3(k-2)-2(5k-1)=10 | | 4(m+3)=4m+12 | | 16a=-112 | | Y=9-3(1) | | 8n-2n=12 | | t=3n+3w | | 2z-7=9 | | 5y^2+8y+3=0 | | 3x-5=8x+9 | | 4x-2=8-x | | -15c+5c+8=4c-20 | | m+36=4m | | 5a+7=3a-11 | | x^4-22x^2+112=0 | | 8n+6=12 |